Prosopografias clubbers em São Paulo e Londres: moda, estilo, estética e cenas musicais contemporâneas - Guerra, Paula (2020)
In this article, we seek to analyze the São Paulo clubber movement in the 1990s as a creator of innovation in fashion and in the contemporary visual imagery. In this opportunity, we will take as a comparison the London clubber scene of the same time, prosopographing two central figures of both scenes: Alexander McQueen and Alexandre Herchcovitch. Our argumentation is that the clubbers' scenes experienced in the 1990s by these two fashion designers, independently activate playful energies and socialities intertwining creation, intermediation and cultural enjoyment on the dance floor. These scenes are spaces of versatility (and simultaneity) of creative roles.Network, simultaneity, versatility, interdisciplinarity, materiality, immateriality are assumed as ineluctable attributes of the musical scenes that are transported to the clubs, and later to the careers of McQueen and Herchcovitch. Keywords: Clubber culture. São Paulo. London. Alexandre Herchcovitch. Alexander McQueen.